Adsorption of Congo Red Dye Using The Kenaf Core - muryanto muryanto; Ferdinan Siahaan (Jurnal Ilmiah Teknik Kimia, 2021)
Kenaf core is waste from the kenaf plant at fiber process. The utilization is still very limited, while the number is increasing due to the increasing number of fiber processes from kenaf plants to become rope or raw materials in the textile industry. However, the textile industry also produces dye waste which is harmful to the environment. Therefore, this study aims to utilize kenaf core as an adsorbent for the congo red dye. The adsorption of the congo red dye by the kenaf core used a variation of the initial concentration and the duration of the adsorption process. Adsorption experimental data showed a decrease in dye concentration from up to 2 ppm, with decolorization reaching 96%. This study proves that kenaf core potential to be used as dye adsorbent.